Occasionalism causation among the Cartesians - Nadler, Steven M., 1958- (Oxford : Oxford University Press, 2010)
Steven Nadler presents a collection of essays on the problem of causation in 17th-century philosophy. These essays examine the philosophical, scientific, theological and religious themes and arguments of occasionalism, as well as its roots in medieval views on God and causality.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Occasionalism -- History -- 17th century; d